2020
DOI: 10.3390/microorganisms8030347
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins: Occurrence, Exposure, and Binding to Lactobacillus Species from the Gut Microbiota of Rural Ugandan Children

Abstract: Chronic exposure of children in sub-Saharan Africa to aflatoxins has been associated with low birth weight, stunted growth, immune suppression, and liver function damage. Lactobacillus species have been shown to reduce aflatoxin contamination during the process of food fermentation. Twenty-three Lactobacillus strains were isolated from fecal samples obtained from a cohort of rural Ugandan children at the age of 54 to 60 months, typed by 16S rRNA gene sequencing, and characterized in terms of their ability to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, the Shannon diversity index of the gut microbiota increased significantly in both study groups from 24 to 36 months ( Atukunda et al, 2019 ). Further analysis of the changes associated with the gut microbiota in the transition from 24 to 36 months revealed that there was a notable shift from autochthonous (endogenous) to allochthonous (plant-derived) Lactobacillus species, and a correlation of Lactobacillus with stunting, most probably resulting from the change in the children’s diet from breast milk to solid, plant-based foods ( Wacoo et al, 2020 ). As follow-up to this study we further investigate here correlations between the gut microbiota of these children with language development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Shannon diversity index of the gut microbiota increased significantly in both study groups from 24 to 36 months ( Atukunda et al, 2019 ). Further analysis of the changes associated with the gut microbiota in the transition from 24 to 36 months revealed that there was a notable shift from autochthonous (endogenous) to allochthonous (plant-derived) Lactobacillus species, and a correlation of Lactobacillus with stunting, most probably resulting from the change in the children’s diet from breast milk to solid, plant-based foods ( Wacoo et al, 2020 ). As follow-up to this study we further investigate here correlations between the gut microbiota of these children with language development.…”
Section: Introductionmentioning
confidence: 99%
“…Other metabolomics based studies also found that AFB1 disrupted several important metabolic pathways of gut microbiota, including synthesis of SCFAs, pyruvic acid-related pathways, amino acids, bile acids, and long-chain fatty acids metabolism (Zhou et al, 2018b(Zhou et al, , 2019a), suggesting that gut microbial metabolism disruption contributes to the pathogenesis of AFB1-induced diseases. Probiotics supplementation including Lactobacillus Species (Liew et al, 2019;Wacoo et al, 2020), Propionibacterium freudenreichii (El-Nezami et al, 2006), Bacillus subtilis , andCandida utilis (Chang et al, 2020b) exerted protective effects against AFB1 both in animal experiments and human trials. These studies illustrate that AFB1 perturbs gut microbiota which can be restored by probiotics and they also help degrade AFB1 and thus lower toxicity.…”
Section: Substances Other Than Drugsmentioning
confidence: 99%
“…Such capable bacterial biofilms could be formed on glass, metal, plastic surfaces in a test tube, 96-well plate, or flow cell formats [ 66 ]. Wacoo et al [ 67 ] found that the allochthonous LAB species ( L. brevis , L. casei , L. fermentum , and L. plantarum ) isolated from the gut microbiota bound AFs effectively.…”
Section: Post-harvest Management Of Aflatoxin Contaminationmentioning
confidence: 99%